The Effectiveness of Utilizing PhET in Increasing the Comprehension of Physics Concepts - Aldena Aenun R Sakona; Usman Usman; Pariabti Palloan; Trisno Setiawan (Jurnal Ilmiah Pendidikan Fisika, 2024)
This research was conducted with the objective of assessing the effectiveness of utilizing PhET media in order to increase the comprehension of physics concepts among eleventh-grade students at SMA Negeri 2 Makassar. This research design was a true experiment, specifically a pretest-posttest control group design. The population comprised all students of XI Science at SMA Negeri 2 Makassar with the total of three classes. The sampling method utilized was random sampling, and the process of collecting data entailed a test. The test consisted of a pretest conducted before the learning phase and a posttest administered after the completion of the learning activities. The indicators for assessing the comprehension of the concepts were based on Bloom's Taxonomy, specifically Translation, Interpretation, and Extrapolation. The comprehensive analysis of the data revealed that the students' comprehension of physics concepts was increased more effectively through the utilization of PhET simulation media. These findings suggest a significant positive effect of incorporating PhET simulation media in physics learning on student outcomes. The N gain score indicates an increase in students' comprehension of the material, demonstrating an increased ability to apply physics concepts following the implementation of PhET simulation media in the learning process. The implementation of PhET simulations in physics education yields positive impact in terms of increasing comprehension of physics concepts. Additionally, the utilization of PhET simulations facilitates the attainment of educational objectives by both teachers and students. Moreover, PhET simulations have the potential to streamline the learning process in classes that previously necessitated an abundance of materials and instruments for experimentation. In other terms, PhET serves as an effective learning medium.